Comparison of the Efficacy of Letrozole and Clomiphene Citrate in women having Anovulatory Infertility - Aisha Ajmal, Joveria Sadaf, Sana Hafeez, Fareeha Usman, Aslam Mahmood Malik, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the efficacy of letrozole and clomiphene citrate in women having anovulatory infertility. Study design: Randomized Controlled Trial. Place and duration of study: 16th October 2020 to 15th September 2021 in Department of Obstetrics & Gynecology, Shahida Islam Medical Complex Lodhran. Methods: In our study 112 patients between ages 18 to 40 years with anovulation were included. Patients having H/O previous pelvic surgery, raised prolactin and TSH levels were excluded. These women were divided into02 groups i.e. Group A (clomiphene citrate) & Group B (letrozole), by lottery method and the effectiveness was noted in both groups. Results: Mean age of women in group A was 24.53±6.12 years and in group B was 25.37±6.33 years. Majority women included in our study, 78(69.64%) were between ages 18 to 30 years. Duration of infertility was 3.28±2.11 years. Mean infertility duration in group A was 3.63±2.10 years and in group B was 3.79±2.14 years. The efficacy of drug shownin Group A was 9(8.03%) while in Group B was 18(16.07%) (p-value = 0.005). Conclusion: We concluded from this study that letrozole is proved to be more efficacious than clomiphene citrate in anovulatory infertility. Keywords: Anovulation, Infertility, Letrozole, Clomiphene Citrate, Conception Rate